2018
DOI: 10.1055/s-0038-1669411
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation: An Overview

Abstract: A cochlear implant (CI) is a surgically implanted device for the treatment of severe to profound sensorineural hearing loss in children and adults. It works by transducing acoustic energy into an electrical signal, which is used to stimulate surviving spiral ganglion cells of the auditory nerve. The past 2 decades have witnessed an exponential rise in the number of CI surgeries performed. Continual developments in programming strategies, device design, and minimally traumatic surgical technique have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 34 publications
0
73
0
Order By: Relevance
“…Of course, this must also be possible outside the regular working hours. Even if there are currently no comparative studies, it appears logic and is described by different authors [1,91].…”
Section: ▪ Radiological Methodsmentioning
confidence: 99%
“…Of course, this must also be possible outside the regular working hours. Even if there are currently no comparative studies, it appears logic and is described by different authors [1,91].…”
Section: ▪ Radiological Methodsmentioning
confidence: 99%
“…The most commonly accepted imaging findings precluding cochlea implantation are [ 1 ]: Complete labyrinthine or isolated cochlear aplasia (Fig. 4 ) Cochlear sclerosis (Fig.…”
Section: Pre-operative Imagingmentioning
confidence: 99%
“…A cochlear implant (CI) is a surgically implanted device consisting of external and internal components [ 1 ]. An external microphone and speech processor are worn behind the ear and convert sound into an electric signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochlear implants may be inserted through a cochleostomy adjacent to the round window or directly through the round window membrane. 63,64 Most surgeons surveyed in 2007 preferred the former approach, though these decisions may be based on historical presumptions; early multichannel leads were thought to traumatize the cochlea if placed through the round window. 65,66 A more recent survey found that today most surgeons prefer round window membrane electrode insertions, given the natural and less traumatic access provided to the scala tympani-the preferred location of electrode placement.…”
Section: Surgical Considerationsmentioning
confidence: 99%